PROGRAM BIMBINGAN PRIBADI – SOSIAL BERDASARKAN LOCUS OF CONTROL INTERNAL PESERTA DIDIK KELAS VII DI MASA PANDEMI COVID-19 - Yani Suryani; R. Ika Mustika; Siti Fatimah (IKIP Siliwangi, 2021)
The aim of this study is to describe how the Personal-Social Guidance Program is based on the Internal Locus Of Control for Seven-Grades Student of SMP Alam Karawang during the Covid -19 Pandemic. The method used in this research is descriptive method with a qualitative approach. The Participants of this study consisted of the Counseling Guidance Teacher, the student's parents, and the seven-grade student. The results of the research are from the results of observations and interviews of personal and social guidance programs based on internal locus of control at SMP Alam Karawang are running well, services are in accordance with the objectives, namely guidance and counseling services are efforts to help students in the development of personal life, social life, learning activities, and career planning and development. Guidance and counseling services facilitate the development of students individually, in groups and or classically, according to their needs, potentials, talents, interests, development, conditions, and opportunities. Guidance and counseling services also help overcome weaknesses and obstacles as well as problems faced by student. Keywords: Locus Of Control Internal, personal-sosial tutoring program, the covid pandemic